Praktik Dzikir Al-Adzkar Al-Nabawiyah untuk Meningkatkan Kecerdasan Spiritual Santri di Pesantren Mahasiswa (Cultivating Spiritual Intelligence through the Practice of Dzikir Al-Adzkar Al-Nabawiyah among Santri at An-Nur Student Islamic Boarding School) - Nabilah, Risky (Happiness: Journal of Psychology and Islamic Science, 2025)
This study aims to explore the practice of dzikir (remembrance of God) based on Al-Adzkar Al-Nabawiyah in enhancing the spiritual intelligence of students (santri) at the An-Nur Student Islamic Boarding School in Surabaya. In the context of modern life, which is often filled with pressure, spiritual intelligence plays a crucial role in helping individuals find deeper meaning and purpose in life. Unfortunately, this aspect is frequently overlooked, even in pesantren (Islamic boarding schools), as intellectual development tends to be prioritized. Therefore, this research was conducted to examine how the practice of dzikir can strengthen the spiritual dimension of santri. This study employed a qualitative approach with a case study method. Data were collected through participatory observation, in-depth interviews, and documentation. The findings reveal three key points: (1) The implementation of dzikir based on Al-Adzkar Al-Nabawiyah is structured, covering its historical background, procedures, duration, and number of recitations; (2) The practice of dzikir has a positive impact on the santris’ spiritual intelligence, including self-reflection, inner peace, resilience in facing life’s pressures, and a closer connection to God; (3) Supporting factors include a conducive pesantren environment, consistent dzikir schedule, and explanation of meanings, while inhibiting factors involve boredom, drowsiness, and academic busyness that distract from focus during dzikir.These findings affirm that a meaningful and consistent dzikir practice can serve as an effective medium in fostering holistic spiritual intelligence among santri.